Determinants and Impacts of dairy farmer collective action in India - Chaudhary, Udita; Malhotra, Ravinder (Indian Journal of Dairy Science, 2025)
This paper first examines the determinants of membership of a Milk Co-operative Union and a Milk Producer Company (MPC) and then subsequently analyses the impacts of membership of the two dairy farmer collective organizations taken together using primary data collected from 416 member and non-member dairy farming households in the prominent dairying state of Gujarat in India. Dairy households belonging to the Other Backward Class (OBC) category are significantly less likely to join cooperatives, and the association between cooperative membership and households from scheduled groups, although not statistically significant, is still negative. In contrast, the dairy households from either scheduled groups or the OBC category are significantly more likely to become members of an MPC. Annual household income negatively influences Co-operative membership; while it positively influences MPC membership. By applying Propensity Score Matching, we find positive income effects for the members. The annual net returns from local cow increase significantly by INR 3,714/-, while the annual net returns from buffalo increase significantly by INR 6,430/-, thereby increasing the total annual net returns from dairy by INR 10,144/- for the members. The share of dairy in total household income increases significantly by 14 percentage points and share of milk sold increases significantly by 1.4 percentage points after membership. While the potential underlying social bias in determinants of membership warrants further investigation, both milk co-operative and producer company models are efficient ways of collective action in the state.